Reply to comments on "Uncertainty and bias in electronic tide gauge records: Evidence from collocated sensors" by Pytharouli S., Chaikalis S. and Stiros S.C., Measurement 125: 496–508, 2018. (June 2020) - Pytharouli, Stella; Chaikalis, Spyros; Stiros, Stathis C.
Highlights: Differences between collocated tide-gauges indicate unusual long-period noise. Databases should contain both raw and corrected data and metadata. Main focus of Comment is that our article is not co-signed by "experts". Our overall methodology proved correct and timely. Abstract: This is a Reply to Comments by Arup et al. on the paper by Pytharouli et al. (2018), recently published in Measurement. Arup et al. (thereafter "Comment"), although they endorsed the conclusions of our study (need of collocated sensors, different performance of sensors, need for metadata, accuracy of tide gauges, etc.), they state in their conclusion that "this paper is misleading in several respects and that the statistical analyses undertaken have little value". This conclusion is unfortunate and unjustified, as we explain below.